2(6)^2

11 answers

= 2(6)^2
= 2(6 * 6)
= 2(36)
= 72

Therefore, 2(6)^2 is equal to 72.
8+72
= 8 + 72
= 80

Therefore, 8 + 72 is equal to 80.
3(6)+4(2)^3-5
3(6) + 4(2)^3 - 5
= 3(6) + 4(2*2*2) - 5
= 18 + 4(8) - 5
= 18 + 32 - 5
= 50 - 5
= 45

Therefore, 3(6) + 4(2)^3 - 5 is equal to 45.
6+(3*4-5)^2
6 + (3*4 - 5)^2
= 6 + (12 - 5)^2
= 6 + (7)^2
= 6 + 49
= 55

Therefore, 6 + (3*4 - 5)^2 is equal to 55.
amelia is building 3 square garden beds that are all the same size. she arranges then side-by-side to separate certain plants. amelia wants to know the total area of the garden beds.

s = length (ft) of one side of a garden bed
Write an expression to show the total area of garden beds.
Total area = 3s^2

Where s is the length (in feet) of one side of a garden bed.

So the expression to show the total area of the garden beds is 3s^2.
what is the total area if each garden bed has a length of 4 feet?
If each garden bed has a length of 4 feet, then s = 4 feet.

Total area = 3s^2
Total area = 3(4)^2
Total area = 3(16)
Total area = 48 square feet

Therefore, the total area of the garden beds when each garden bed has a length of 4 feet is 48 square feet.